2016
DOI: 10.1108/afr-05-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of loan demand in agriculture: empirical evidence from Germany

Abstract: Purpose The purpose of this paper is to empirically investigate the influencing factors of loan demand in agriculture. With the structural changes that agriculture is undergoing and the accordingly higher financing requirements and volumes, the analysis of loan demand in agriculture is of particular interest. Design/methodology/approach Detailed actual loan data at farm level, which is provided by a major German development bank for the agricultural sector, is used for the analysis. The data set covers the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 56 publications
2
30
1
1
Order By: Relevance
“…In an analysis of loan data from a major German development bank, Fecke et al (2016) found that loan demand was significantly influenced by the choice of different types of capital investment, loan structures and business climate expectations. In an examination of the effect of declining commodity prices on the use of debt by soybean and corn farmers in the United States, Prager et al (2018) found that, following commodity price shocks, farm businesses with higher debt-to-asset ratios increased their non-real estate debt relative to those with less debt intensive capital structures, while off-farm income reduced reliance on external debt.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of loan data from a major German development bank, Fecke et al (2016) found that loan demand was significantly influenced by the choice of different types of capital investment, loan structures and business climate expectations. In an examination of the effect of declining commodity prices on the use of debt by soybean and corn farmers in the United States, Prager et al (2018) found that, following commodity price shocks, farm businesses with higher debt-to-asset ratios increased their non-real estate debt relative to those with less debt intensive capital structures, while off-farm income reduced reliance on external debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Equity is an important signal to access debt for capital investment where commercial lenders are the primary source of credit (Benjamin and Phimister 2002;Cadot 2013); in Australia, 96% of all rural debt is provided by commercial banks (White 2018). Equity measures farm business net worth, so higher equity values would be expected to positively influence farm business outlook, which has been shown to have a positive impact on loan supply (Fecke et al 2016).…”
Section: Study Region and Datamentioning
confidence: 99%
“…This cost is charged by lenders as a benefice of the loan and is paid by the borrower plus the initial amount of the loan during the reimbursement. Thus, other things being equal, if the interest rate charged by lenders is high, it could deter farmers from borrowing [57,58]. Nevertheless, some studies found that the interest rate does not necessarily affect borrower choice [14].…”
Section: Variables and Empirical Hypothesesmentioning
confidence: 99%
“…Modal merupakan bagian input usaha tani, tujuan penambahan modal yaitu untuk menaikan volume produksi, penjualan dan pendapatan serta menaikan laba. Kekurangan modal menjadi masalah penting dalam proses kegiatan usaha tani, maka penambahan modal dapat dilakukan dengan meminjam atau kredit pada bank atau lembaga keuangan lainnya, baik formal maupun informal (Fecke & Al., 2016).…”
Section: Pendahuluanunclassified